2015
DOI: 10.1099/vir.0.000105
|View full text |Cite
|
Sign up to set email alerts
|

Cis- and cell-type-dependent trans-requirements for Lassa virus-like particle production

Abstract: Lassa virus (LASV) small zinc-finger protein (Z), which contains two L-domain motifs, plays a central role in virus budding. Here, we report that co-expression of glycoprotein (GPC) altered the requirements for cholesterol but not the L-domains and host factor, Tsg101, for Z-induced viruslike particle (VLP) production. In particular, the cholesterol requirement for VLP production was cell-type-dependent. In addition, GPC was found to be important for co-localization of Z with CD63, a late endosomal marker. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 40 publications
(52 reference statements)
1
7
0
1
Order By: Relevance
“…7, co-expression of NP, but not GPC or L, with Z protein led to the significant increase of VLP production (4.3-fold). Interestingly, co-expression of GPC with Z reduced VLP production in both 293T and HeLa cell lines (Figs 6 and 7), which is consistent with the previous report for LASV [47]. We also observed the co-localization of JUNV NP and BST-2 in cells by a laser confocal microscopy (Fig.…”
Section: Junv Np Counteracts the Effect Of Bst-2 Restriction On Vlp Psupporting
confidence: 92%
See 1 more Smart Citation
“…7, co-expression of NP, but not GPC or L, with Z protein led to the significant increase of VLP production (4.3-fold). Interestingly, co-expression of GPC with Z reduced VLP production in both 293T and HeLa cell lines (Figs 6 and 7), which is consistent with the previous report for LASV [47]. We also observed the co-localization of JUNV NP and BST-2 in cells by a laser confocal microscopy (Fig.…”
Section: Junv Np Counteracts the Effect Of Bst-2 Restriction On Vlp Psupporting
confidence: 92%
“…We next addressed if any of JUNV-encoded protein(s) could overcome BST-2 activity and rescue VLP production, as a reduction in cell surface BST-2 was observed upon JUNV infection. Previous research has shown that arenavirus NP and GP influence Z-mediated VLP production [46][47][48][49]. Expression plasmid for JUNV NP, GPC or L protein was transfected into 293 T cells with the Z expression plasmid in the presence or absence of pCDNFL-hTeth.…”
Section: Junv Np Counteracts the Effect Of Bst-2 Restriction On Vlp Pmentioning
confidence: 99%
“…The pCAGGS plasmids expressing wild-type (WT) or mutant (Mut) Z proteins of the above listed arenaviruses, which possess C-terminal FLAG (for JUNV, MACV, TCRV, LATV, PICV, and LASV) or C-terminal HA (for TCRV) tags (Niwa et al, 1991;Urata et al, 2009), were kindly provided by Dr. J.C. de la Torre (The Scripps Research Institute). The LASV Z expression plasmid was previously described (Urata et al, 2006;Urata and Yasuda, 2015). To construct expression plasmids for the L-domain mutants (Figure 2), KOD plus mutagenesis kit (Toyobo, Japan) was used according to the manufacturer's protocol using the following primer sets: JUNV Z-Mut, 5 -GTACCGGTGGAGGCAGCAGCAGCACCACCAGG-3 and 5 -TGTGATTGTGGTGGGCAGGGGC-3 ; MACV Z-Mut, 5 -GGAGGCAGCTGCCGCCCCACCAGGAGGAG-3 and 5 -ACGGGAACTGTGATGGATGTCGG-3 ; LATV Z-Mut, 5 -CATAACTGCAGCAGCAGCGCAACTCAACGGAGG-3 and 5 -CCGACTTCAATGTAGGTTGGAATTG-3 ; PICV Z-Mut1, 5 -GTTTCTGGAGAGTGCGGCTGCAGCTCCCTATG-3 and 5 -CATAGGGAGGTGCAGCCGCACTCTCCAGAAAC-3 ; PICV Z-Mut2, 5 -GTTTCTGGAGAGTGCGGCTGCACCTCCC TATG-3 and 5 -CATAGGGAGGTGCAGCCGCACTCTCCAGA AAC-3 ; PICV Z-Mut3, 5 -GTCTGCACCTCCCGCTGAGC CAGGAGGAG-3 and 5 -CTCCTCCTGGCTCAGCGGGAGGT GCAGAC-3 .…”
Section: Cell Lines Plasmids and Antibodiesmentioning
confidence: 99%
“…Both Lassa Z and Ebola VP40 contain conserved amino acid motifs referred to as late (L) domains that have the core consensus motifs of either PTAP or PPxY (where x = any amino acid). The viral L-domains have been shown to facilitate budding of both VLPs and infectious virions by a mechanism that involves interactions between the L-domain motifs and specific host proteins [ 3 , 7 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. For example, the viral PPxY motif interacts with specific host proteins containing one or more WW-domains, and the majority of host WW-domain interactors identified to date have been shown to enhance or facilitate VLP and/or virus egress.…”
Section: Introductionmentioning
confidence: 99%